Iranian soft power in Azerbaijan : Does religion matter? - Valiyev, Anar (Routledge, 2017)
Very little research has been undertaken to study the role of soft power in international relations. As one of the fathers of this concept, Nye states that soft power refers to the capability of an entity, usually but not necessarily a state, to influence what others do through direct or indirect international influence and encouragement. The proclamation of Shi'a Islam as the official religion on the territory of the Safavid Empire in the early sixteenth century brought both Iran and Azerbaijan under one umbrella of religious affiliation. That mere fact would shape the future of relations between the two countries for centuries. The Shi'a heritage of Azerbaijan represents the main source of Iranian soft power. As in Lebanon or Iraq, Iranian foreign policy actively uses this factor. Religious protests very often coincide with some significant political event happening in Azerbaijan or Iran.
Religion and Soft Power in the South Caucasus
Keywords: Religion and politics -- Caucasus, South.; Religion and politics -- Azerbaijan.; Azerbaijan -- Religion.